2017
DOI: 10.1111/jnc.13584
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repressor DREAM regulates trigeminal noxious perception

Abstract: Expression of the downstream regulatory element antagonist modulator (DREAM) protein in dorsal root ganglia and spinal cord is related to endogenous control mechanisms of acute and chronic pain. In primary sensory trigeminal neurons, high levels of endogenous DREAM protein are preferentially localized in the nucleus, suggesting a major transcriptional role. Here, we show that transgenic mice expressing a dominant active mutant of DREAM in trigeminal neurons show increased responses following orofacial sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Attenuation of central sensitization due to reduced Bdnf gene expression contributed to the hypoalgesic behavior of the transgenic mice. Recently, it was reported that another line of daDREAM mice (with daDREAM expression in trigeminal ganglia) showed a significant increase in the rubbing response in the first and second phases of the formalin test, which might be correlated with decreased expression of Pdyn (Benedet et al, 2017). Conversely, the nocifensive response to 4.5% formalin injection in the snoot in Kcnip3 -/- mice was milder than that in normal mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attenuation of central sensitization due to reduced Bdnf gene expression contributed to the hypoalgesic behavior of the transgenic mice. Recently, it was reported that another line of daDREAM mice (with daDREAM expression in trigeminal ganglia) showed a significant increase in the rubbing response in the first and second phases of the formalin test, which might be correlated with decreased expression of Pdyn (Benedet et al, 2017). Conversely, the nocifensive response to 4.5% formalin injection in the snoot in Kcnip3 -/- mice was milder than that in normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…Increased intracellular Ca 2+ concentration can prevent binding of DREAM to the DRE site and derepress DRE-dependent gene expression. Functional expression of DREAM in cortex, hippocampus, cerebellum, spinal cord, dorsal root ganglion (DRG), pineal gland, thyroid and blood cells was validated, and numerous target genes of DREAM were identified, including Fos, Pdyn (prodynorphin), Slc8a3 (solute carrier family 8 member A3), Npas4 (neuronal PAS domain protein 4) and Bdnf (brain-derived neurotrophic factor) (Table 1) (Carrion et al, 1998, 1999; Sanz et al, 2001, 2002; Link et al, 2004; Rivas et al, 2004; D’Andrea et al, 2005; Gomez-Villafuertes et al, 2005; Savignac et al, 2005; Venn et al, 2008; Dierssen et al, 2012; Mellstrom et al, 2014; Benedet et al, 2017). Actually, DREAM is identical to KChIP3 (Kv4 channel interacting protein 3), a member of the KChIPs family, which is composed of KChIP1, 2, 3 and 4.…”
Section: Introductionmentioning
confidence: 99%
“…KCNIP3 mutants with two amino acids substitution in the EF-hands two, three, and four are unable to respond to Ca 2+ and function as a constitutively dominant active (daDREAM) transcriptional repressor (Savignac et al, 2005). In transgenic mice with neuronal expression of this daDREAM, the CAMK2A mRNA level is reduced by 1.7-fold compared to wild type (Benedet et al, 2017). Mouse promoter for KCNN4 is conserved (79%), but in a lesser extend concerning DRE sequences.…”
Section: Regulation Of Gbm Prognosis Genes By Kcnip Proteinsmentioning
confidence: 94%
“…Initially identified as calsenilin, a presenilin binding protein [5], was rapidly recognized also as a transcriptional repressor through the association with DRE (Downstream Regulatory Element) sites [6], and a potassium channel interacting protein (KChIP3) that regulates the intracellular traffic and biophysical properties of K v 4 channels [7]. Besides modifying the expression of several genes involved in pain perception, like c-fos [6], brain derived neurotrophic factor (BDNF) [8,9], prodynorphin [6,10], cathepsin L [11] or interleukins 2 and 4 [12], DREAM also interacts with a variety of ion channels and receptors involved in pain detection and transmission in DRG neurons. This is the case of NMDA glutamate receptors [13], TRPV1 channels [14], and a variety of voltage-activated channels, including K v 4.3 channels responsible for the transient, A-type, potassium current (I A ) [15], and the low, T-type [16], and high voltage-activated (HVA), L-type [17] Ca v channels.…”
Section: Introductionmentioning
confidence: 99%